If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -13 = -8y + 27 Reorder the terms: -13 + 2y = -8y + 27 Reorder the terms: -13 + 2y = 27 + -8y Solving -13 + 2y = 27 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. -13 + 2y + 8y = 27 + -8y + 8y Combine like terms: 2y + 8y = 10y -13 + 10y = 27 + -8y + 8y Combine like terms: -8y + 8y = 0 -13 + 10y = 27 + 0 -13 + 10y = 27 Add '13' to each side of the equation. -13 + 13 + 10y = 27 + 13 Combine like terms: -13 + 13 = 0 0 + 10y = 27 + 13 10y = 27 + 13 Combine like terms: 27 + 13 = 40 10y = 40 Divide each side by '10'. y = 4 Simplifying y = 4
| 8x+12=6x+8 | | 10k=2/7 | | 6+4x=-x-15 | | x=5t^2-5t/3-2 | | 9/8=18/t | | U-5/7=4/2/7 | | 3+91x=39+51 | | 3(x-8)=2x-(7x+12) | | 2x^2+3y^2-8x+3y+10=0 | | z^2-(3+i)z+2+2i=0 | | 4x-3-3x=12+2z | | 5y-6y^2+1=0 | | -2-4x-x=x-8 | | (2x-5)*4+9= | | 6x=7x-8 | | x^2-8x-108=0 | | 7a-(6b+8b)= | | 12-x+13-x=15 | | 2a+8b-3a= | | Cos(x)-0.5=0findx | | V-3/4=4/5 | | (2-x)/2=(2x-3)/3 | | -16t^2+35t+12=0 | | 1.5x^2-1.5x-3=0 | | 2400+80x=y | | x^4-6x^3-1=0 | | Cos(x)-0.5=0 | | 0=-0.5x^2+40x-300 | | 3(6+w)=2(w-1) | | .0025=1/x | | 2400+800x=y | | -2(y+3)+5(y-1)=-4 |